Compilado de proyectos de investigación científica empresarial : semana de la ciencia, la tecnología, la innovación y el emprendimiento - Mendoza Sánchez, Bernardo (Corporación Universitaria Americana, 2023)
Economic, Administrative and Accounting Sciences have remained in time under a constant transformation generated by the dynamics of the context. the understanding of a constant transformation generated by the dynamics of the context; generating a growth, diversification and specialization of these sciences around the political, social and economic political, social and economic environments. From the above perspective, it is necessary to create spaces for dialogue around the work of the professionals of the the work of professionals in these areas of knowledge that allow for a contextualized appropriation, but on the other hand, on the contextualized appropriation, but above all, that manages to provide real solutions to the sector, this, from a research exercise that provides both epistemological and methodological elements for the generation of new knowledge; such is the case of those compiled within the framework of the Week of Science, Technology, Innovation and Entrepreneurship, namely: Social Alliances between Foundations in the District of Barranquilla, Evaluation of the Structure of the Financial Statements of the SME Computadores y Tecnologías del Caribe dedicated to the Commercialization of Computer Parts and Equipment in Barranquilla after the Implementation of the IFRS, Implementation of an Agricultural Accounting System from the approach of Section 34 of the International Financial Reporting Standards for SMEs, in a coffee farm, digitalization of business processes in the textile sector of the city of Barranquilla, through the implementation of ICT tools, Knowledge Management in 5 Star Hotels in Barranquilla-Colombia.